Journal Economics, business & accountancy: THE ETHICS OF ACCOUNTING STUDENTS: A COMPARATIVE STUDY - Dian Indri Purnamasari (PPPM Perbanas, 2011)
It is noted that there have been problems of ethics in the auditing happening in big companies.In addition, the issues of ethics are closely related to the auditing profession. This isbelieved that they are also related to the independence in doing the profession. In consequence,the auditing profession is expected to have high independency and objectivity becauseit has the responsibility for providing public service to the society who has trustedthem.